2001
DOI: 10.1096/fj.00-0460fje
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Sendai virus‐mediated gene transfer to vasculature: a new class of efficient gene transfer vector to the vascular system

Abstract: Unsolved issues in clinical gene therapy for cardiovascular diseases include gene transfer efficiency and the requirement of a longer exposure time. We developed a novel mononegavirus vector, recombinant Sendai virus (SeV), and tested whether it can overcome the present hurdles. SeV showed dose‐dependent and persistent gene expression in either proliferating or arrested cells, suggesting stability of RNA genome of the vector. An outstanding feature of the SeV‐mediated gene transfer was that even a brief exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 31 publications
1
71
0
Order By: Relevance
“…(i) SeV vectors can infect nondividing, quiescent cells as well as dividing cells unlike oncoretroviral vectors. [7][8][9][10][11] Thus, they can be used to infect cells that are terminally differentiated as well as at various stages of differentiation, whether they are dividing or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) SeV vectors can infect nondividing, quiescent cells as well as dividing cells unlike oncoretroviral vectors. [7][8][9][10][11] Thus, they can be used to infect cells that are terminally differentiated as well as at various stages of differentiation, whether they are dividing or not.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] We have previously developed Sendai virus (SeV) vectors that replicate in the form of negative-sense single-stranded RNA in the cytoplasm of infected cells and do not go through a DNA phase. 6 SeV vectors can efficiently introduce foreign genes without toxicity into airway epithelial cells, 7 vascular tissue, 8 skeletal muscle, 9 synovial cells, 10 retinal tissue, 11 and hematopoietic progenitor cells. 12 Here we report that the SeV-mediated gene transfer into primate ES cells is very efficient and stable even after the terminal differentiation of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][30][31][32][33] However, in our systems, excellent gene transfer could be achieved by the simple addition of SeV vector solution without specific reagents or centrifugation. Moreover, optimal SeV-mediated gene transfer to activated T cells could be performed during a relatively brief exposure time (less than 30 min, Figure 4d), with representative results seen in nasal mucosa, 20 in the vasculature, 21 in retinal tissue, 24 as well as in human umbilical cord bloodderived CD34-positive cells. 45 In addition, rare syncytium formation and few cytopathic effects were observed at the MOI used in this study (data not shown).…”
Section: Activated T-cell-directed Gene Transfer Via Sevmentioning
confidence: 99%
“…14 Using this vector, we demonstrated markedly superior gene transfer efficiency compared to findings with currently available vectors for use in various organs. [19][20][21][22][23][24][25] In contrast to systems involving retroviridae, replication and transcription of SeV are seen in the cytoplasm accompanying cellular tubulin, 26 and nuclear import and genomic integration are not required, 14 thereby suggesting the elimination of potential risks, including unexpected events related to chromosomal injury.…”
Section: Introductionmentioning
confidence: 99%
“…7 Also recombinant virus designed to encode the gp120 glycoprotein resulted in extremely high levels of transgene expression in CV-1 monkey kidney cells. 8 Interestingly, although HVJ liposomes containing Sendai-derived haemaglutinin protein complexed with plasmid DNA carrying the b-galactosidase gene have been applied prenatally by intra-amniotic delivery, which resulted in low and transient expression in rat skin, 9 no previous studies have described the use of recombinant SeV particles in a prenatal context probably due to its intrinsic cytotoxic nature and transient gene expression.…”
Section: Introduction Application Of Sev In Gene Therapymentioning
confidence: 99%